Case Study: An Evaluation of an ESP Textbook Used at the College of Business Studies in Kuwait from the Learners' Perspective Regarding Its Alignment with Future Career Requirements - Nour Haidar Haidar (European Scientific Journal, ESJ, 2024)
A key aspect of learning English is evaluating the materials. It is regarded as a cornerstone in the field of English for Specific Purposes. The purpose of this study is to evaluate an ESP textbook that is taught at Kuwait's College of Business Studies. It looks at how learners perceive the textbook. The study also aims to determine whether the textbook helps in preparing learners for their future business careers. A series of research instruments, including a questionnaire, a checklist, and interviews, were developed for this purpose. The results proved that the learners' opinions of the textbook varied. While a minority of students felt that the textbook was unsuitable for their level of English proficiency, the majority of students liked it and thought it was useful and met their requirements. The results also proved that the textbook prepared the learners for their future careers to a certain degree.